THE INFLUENCE OF MOTIVATION, LEADERSHIP STYLE, COMPENSATION ON WORK DISCIPLINE AT PT. CANDI JAYA AMERTA TANGGULANGIN SIDOARJO - Dinda Deviedi Putri; Rohmah Kurniawati (Jurnal Ekonomi, 2023)
HR is the company's most crucial part. Human resources help the organization achieve its goals. Companies should prioritize employee needs. Paying employees for their job is crucial to their needs. Company productivity is affected by leadership style. One is compensation and discipline motivation. This study examined the impact of leadership style and compensation on PT. Candi Jaya Amerta Sidoarjo's work discipline and employee performance discipline. Temple of Jaya Amerta The research data is quantitative descriptive with two independent variables. All 50 production staff of PT. Candi Jaya Amerta were given questionnaires, and 50 samples were collected. Then tested instruments and classical assumptions. SPSS version 23 will evaluate multiple regression. The study found no positive and insignificant influence of pay equity and workload balance on PT. Candi Jaya Amerta employees' work discipline motivational variables.